Perilaku Masyarakat tentang Menguras, Menutup, Mengubur (3M) Plus terhadap Bebas Jentik - Yuyun Priwahyuni; Tiara Ikhsan Ropita (STIKes Hang Tuah Pekanbaru, 2014)
The low free larva indeks in the Singkuang village which is 41% and not in accordance with the national standard is more or equal to 95%. This study aims to determine the behavior of the public about the 3M Plus of free larvae of the Singkuang Village District of Kampar, Kampar regency in 2014. The kind of research used in this study is Analytical observational cross-sectional design. This study by distributing questionnaires and observations. The total sample are 112 household in the Singkuang village. The analysis used univariate analysis with frequency distribution is and bivariate analysis with the chi-square statistical test. The results showed that there is correlation of public knowledge about 3M Plus the free larvae ( p value = 0.005 ) , public attitudes about 3M Plus toward the free larvae ( p value = 0.002 )there is not correlation of community action against 3M Plus free larvae ( p value = 0.053 ). All variables associated with free larvae. From the results of this study suggested the need to increase public knowledge by doing more intensive counseling , increased collaboration between public health officials with the society of Ranah Singkuang village District of Kampar, Kampar regency